"THE ADVOCACY SYSTEM OF THE UZBEK SSR: REFORMS AND RESULTS (20s OF THE XX CENTURY)" (Scientific journal of the Fergana State University, 2025)
The article, based on a wide range of primary sources and historical literature, describes the changes that occurred in the activities of the legal profession in the Uzbek SSR after the establishment of Soviet power. The legal services provided by lawyers, their results, the national composition and level of education of lawyers are analyzed.